2008
DOI: 10.1176/appi.ajp.2008.08010085
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Birth Weight and Behavioral Symptoms of Attention Deficit Hyperactivity Disorder in Young Adulthood: The Helsinki Study of Very-Low-Birth-Weight Adults

Abstract: Rather than very low birth weight per se, intrauterine growth retardation, as reflected by small for gestational age status in the very-low-birth-weight subjects, confers a risk for behavioral and emotional adversity related to ADHD in young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
105
4
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 39 publications
15
105
4
1
Order By: Relevance
“…27 Prematurity on the other hand is associated with personality profiles in adulthood characterized by over-controlling or inhibited tendencies, such as cautiousness, dutifulness, and fewer risk-taking or fun-seeking behaviors. 18,26,[28][29][30] Adolescents who have over-controlling tendencies have fewer intimate relationships, 31 and individuals who have inhibited tendencies have lower likelihood of having a stable romantic partner in young adulthood and get involved with such relationships later than control subjects. 32,33 Although we observed that preterm-born individuals were less likely to engage in romantic relations in young adulthood, they had similar likelihood of moving out of their childhood home as their term-born peers.…”
Section: Discussionmentioning
confidence: 99%
“…27 Prematurity on the other hand is associated with personality profiles in adulthood characterized by over-controlling or inhibited tendencies, such as cautiousness, dutifulness, and fewer risk-taking or fun-seeking behaviors. 18,26,[28][29][30] Adolescents who have over-controlling tendencies have fewer intimate relationships, 31 and individuals who have inhibited tendencies have lower likelihood of having a stable romantic partner in young adulthood and get involved with such relationships later than control subjects. 32,33 Although we observed that preterm-born individuals were less likely to engage in romantic relations in young adulthood, they had similar likelihood of moving out of their childhood home as their term-born peers.…”
Section: Discussionmentioning
confidence: 99%
“…Our follow-up rate is comparable to that reported in most international studies. For example, in the highly informative Helsinki Study 32,[47][48][49] there were 474 consecutive VLBW admissions to the regional NICU from January 1978 to December 1985; 335 were discharged alive, 95% survivors were traced, 255 residing in the Helsinki area were invited to participate, and 166 did so (50% overall). The Netherlands POPS study at 19 years achieved 62% follow-up, 45 and studies of pulmonary function in late adolescence in VP infants from Melbourne, Australia, included 74% of survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, only the Helsinki Study of Very-LowBirth-Weight Adults examined whether the effects of VLBW on development differ between VLBW adults who were SGA and those who were AGA (Strang-Karlsson et al 2008). VLBW adults in the SGA subgroup (mean age: 22.2 years old) scored significantly higher on the executive dysfunction and emotional instability subscales of the Adult Problem Questionnaire (a measure of attention deficit hyperactivity disorder [ADHD] behavioral symptoms), than did those in the AGA subgroup (mean age: 22.5 years old) and the term comparison group (mean age: 22.5 years old; Strang- Karlsson et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…VLBW adults in the SGA subgroup (mean age: 22.2 years old) scored significantly higher on the executive dysfunction and emotional instability subscales of the Adult Problem Questionnaire (a measure of attention deficit hyperactivity disorder [ADHD] behavioral symptoms), than did those in the AGA subgroup (mean age: 22.5 years old) and the term comparison group (mean age: 22.5 years old; Strang- Karlsson et al 2008). ADHD is known to be related to LD, and studies have reported that VLBW infants had a higher risk for ADHD and LD when they reached school age compared with a normal term group (Aarnoudse-Moens et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation